Comparative Metabolite and Gene Expression Analyses in Combination With Gene Characterization Revealed the Patterns of Flavonoid Accumulation During Cistus creticus subsp. creticus Fruit Development - Aničić, Neda; Patelou, Efstathia; Papanikolaou, Antigoni; Kanioura, Anthi; Valdesturli, Camilla; Arapitsas, Panagiotis; Skorić, Marijana; Dragićević, Milan; Gašić, Uroš; Koukounaras, Athanasios; Kostas, Stefanos; Sarrou, Eirini; et al. (Frontiers in Plant Science, 2021)
Cistus creticus L. subsp. creticus (rockrose) is a plant widespread all over Greece and has been used in Mediterranean folk medicine as herbal tea infusions for colds, healing, and digestive complications, as extracts for the treatment of diseases, as fragrances and for other purposes. Compounds from its flavonoid fraction have recently drawn attention due to antiviral action against influenza virus and HIV. Although several bioactive metabolites belonging to this group have been chemically characterized in the leaves, the genes involved in their biosynthesis in Cistus remain largely unknown. The aim of this work was to study the flavonoid metabolism during C. creticus fruit development, by adopting comparative metabolomic and transcriptomic approaches. The present study highlights the fruit of C. creticus subsp. creticus as a rich source of flavonols, flavan-3-ols and proanthocyanidins, which all displayed decreasing trend during fruit development. The majority of proanthocyanidins recorded in Cistus fruit are B-type procyanidins and prodelphinidins, while gallocatechin and catechin are the dominant flavan-3-ols. The expression pattern of biosynthetic genes and transcription factors were analyzed in flowers and throughout three fruit development stages. Flavonoid biosynthetic genes were coordinately regulated in a temporal-manner, showing a decrease in transcript levels during fruit maturation. High degree of positive correlations between the content of targeted metabolites and the expression of biosynthetic genes indicated transcriptional regulation of flavonoid biosynthesis during C. creticus fruit development. This is further supported by the high degree of significant positive correlations between the expression of biosynthetic genes and transcription factors. The results suggest that leucoanthocyanidin reductase predominates the biosynthetic pathway in the control of flavan-3-ol formation, which results in catechin and gallocatechin as one of the major building blocks for Cistus proanthocyanidins. Additionally, there is a decline in the ethylene production rates during non-climacteric Cistus fruit maturation, which coincides with the downregulation of the majority of flavonoid- and ethylene-related biosynthetic genes and corresponding transcription factors, as well as with the decline in flavonoid content. Finally, a functional characterization of a Cistus flavonoid hydroxylase (F3’5’H) was performed for the first time.